The Abuja Declaration on cells, tissue and organ donation and transplantation - Assounga, Alain (African Journal of Nephrology, 2012)
Special Article by the participants of the Regional Consultation in the African Region on Cells, Tissue and Organ Donation and Transplantation, Legal and Organisational Aspects, Abuja, Nigeria, July 29-31, 2009.